Breast Cancer Screening Program in Morocco: Status of implementation, organization and performance. Issue 12 (26th September 2018) - Basu, Partha; Selmouni, Farida; Belakhel, Latifa; Sauvaget, Catherine; Abousselham, Loubna; Lucas, Eric; Muwonge, Richard; Sankaranarayanan, Rengaswamy; Khazraji, Youssef Chami
Abstract : Breast Cancer Screening Program was introduced and rolled out in Morocco in 2010. Women between 40 and 69 years are screened at the primary health centers (PHC) with clinical breast examination (CBE). A comprehensive evaluation of the program was conducted in 2016–2017 for quality assurance and mid‐term course correction. The evaluation process involved: in‐depth interviews of program managers; focus group discussions with service‐providers of screening, diagnosis and treatment; supportive supervisory visits to randomly selected PHCs and diagnostic centers; desk review of the national guidelines and other published documents; and analysis of the performance data compiled by the program‐in‐charge. We found that the program has strong political support, a well‐organized management structure and documented national policy and protocol. In absence of a mechanism to identify and invite the eligible women individually, the program is opportunistic in nature. Every PHC is provided with an annual target to be screened. A highly visible annual campaign to educate and motivate women has a major impact on participation. Record keeping and data collection are paper‐based. In the years 2015 and 2016, 1.1 and 1.5 million women were screened, respectively. In the year 2015, 62.8% of the annual target population was covered, CBE positivity was 3.2%, a further assessment rate of screen‐positive women was 34.1% and the breast cancer detection rate was 1.0/1000 women. Systematic paper‐based data collection enabled the assessment of some of the process and outcome indicators. The screening coverage was moderate and the cancer detection rate was low. Abstract : What's new? The rising incidence of breast cancer is a tremendous public health challenge in the developing world. Clinical breast examination is a promising approach provided effective diagnosis, timely treatment, and adequate resources. Here, the authors conducted a comprehensive evaluation of the Breast Cancer Screening Program in Morocco, where systematic data collection is challenging in absence of a computerized information system. They found that the program has strong political support and a well‐organized management structure. Systematic paper‐based data collection showed a moderate screening coverage and low cancer detection rate. The experience will be useful for all developing countries implementing clinical breast examination.